FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MEROKOK SHISHA PADA SISWA SMA X DI KOTA SEMARANG - Ardy Widya Pangestu; Kusyogo Cahyo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Semarang City Health Office, specifically noting that 34.4% of young men and 4% of young women who smoke. Score high shisha smoking behavior in adolescents beginning comes from oneself, others and the environment that may influence smoking behavior itself. X high school students in the city Semaran often smoke shisha at 49.2%. The purpose of this study to analyze the factors related to the behavior of smoking shisha at X high school students in the city of Semarang. This research is quantitative research with cross sectional approach. The population is X high school students in the city of Semarang ever consume shisha is there are 177 high school students. By using the formula of Lemeshow there are samples that are 63 respondents. The sampling technique using random sampling. Analyzed using univariate and bivariate statistical test Chi-Square (significance level 0.05). Most of the respondents were 14-16 years of age (early teens) (54.0%). Gender respondents was (92.1%) were male and knowledge of the respondents in the high category (50.8%). The attitude of the respondents in both categories (52.4%). Support Friends respondents was (61.9%) in both categories and support for families (57.1%) in both categories. The availability of resources in the complete category of (54.0%) and affordability of resources in both categories of (71.4%). Chi-Square test results found no relationship between knowledge, attitudes, peer support, and resource availability. As for age, sex, family support, and affordability of resources no relationship with shisha smoking behavior in high school students X in Semarang.